Education eldership and pastoral care in schools. (2nd April 2016) - Barrow, Giles
Abstract: The paper sets out a discussion on the theme of eldership in the context of schools, with particular reference to implications for school eldership and pastoral care. The author provides a commentary on the decline of available support for school leaders in terms of informal eldership networks and the changing demographic of the teaching profession. The discussion considers specific consequences of this changing demographic, and a subsequent shift in focus amongst new entrants to teaching, with particular attention to the impact for delivering pastoral care. The author presents a perspective on eldership, suggesting a range of qualities and expertise that constitute the role of the elder, raising questions and challenges for re-establishing eldership in education.